The Narrative Techniques of RK Narayan in The Guide: Exploring the Narrative Techniques and Social Critiques in R.K. Narayan's 'The Guide' (Journal of Advances and Scholarly Researches in Allied Education, 2013)
R. K. Narayan is one of the three important Indian novelists in English. Mulk Raj Anand and Raja Rao are the other two important novelists. Narayan's books are about the ordinary middle-class man's life. With a sense of realistic humor, he aims at everyday life. He criticizes the hypocrisy of the middle class with gentle cynicism. He looks at things in a fascinating way. He is detached observer of our ordinary interests. The Guide attempts at reviving the ethnic cultures, traditions, beliefs and languages. He writes about a cross-section of the Indian society. His characters are drawn from a wide variety of situations. They're not wealthy, they're not bad either. They come from the traditional circumstances of the middle class. They are resourceful, too. They have ample common sense they are sharp life observers. Its characteristics are unfailing, hard work. You have an exciting sense of life. They still engage in life with anticipation. All of them are optimists born. He utilizes double storytelling methods and deliberately uses narrative strategies. He uses the method of flash-back narration. This helps Raju admire his own character. Raju displays ample authenticity and integrity in this story of past existence. He shows himself with immense bravery. The Guide is one of the most fascinating and famous works of Narayan and is mentioned in a variety of retrospectives. In this book, Raju tells his history and recalls his thoughts. Via black flash, Raju continues with his past narrative. The railway line is eventually finished and a train station is built in Malgudi. Raju's reminiscence renders the novel believable. The retrospective approach excites the reader's imagination and interest. It also shows Narayan's capacity to say a born story. Narayan utilizes the insightful approach from a particular narration point of view. The narrative moves from first to third hand, often it is Raju, the main character speaking, at other times it's revealed from an all-knowing narrator's point of view. The author also uses film components and flashbacks.